Duo’ Flux / Anis Maisarah Jafri … [et al.] - Jafri, Anis Maisarah; Amat, Nornazuwah; Zulhisham, Nuranis Syamira; Mohd Amin, Nurul Izzah; Mohd Nordin, Noorain (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
The Duo' Flux is a kind of double pipe, and it is very uncommon in Malaysia since we are not used to seeing water soap that can flow through the water tap. Usually, it will always water tank separately with the soap on any occasion. However, it can be difficult when the soap is not provided. So, people don't have any other option instead of washing their hands using water only. With the Duo' Flux, this product will help people wash their hands on any occasion more easily. Duo' Flux is an innovation that we designed to educate consumers to put a value on hygiene practices themselves. Besides that, one of our objectives is the consumers can wash their hands without traces of oil and odor, especially on special occasions. The Duo' Flux is an innovation that combines two pipes where one pipe will flow the clean water whereas another pipe will flow the soap water, and it will have the labeling of "water" and "soap" to make them different. This double pipe with soap is convenient for consumers because it can be attached to the existing water tank and easily removed. Then, one of Duo' Flux's unique features is a soap container that can be filled and refilled with liquid soap when it has been used up. With the Duo’ Flux innovation, there is no problem with soap forgotten to be provided. Our company also intends to patent Duo' Flux under the Intellectual Property Corporation of Malaysia.